Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP

One-pot synthesis of 2,4,5-trisubstituted imidazoles using MoO3/SiO2, an efficient and recyclable catalyst - Bhosale, Sidhanath V.; Kalyankar, Mohan B.; Nalage, Santosh V.; Bhosale, Dattatry S.; Pandhare, Swati L.; Kotbagi, Trupti V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Synthetic Communications, 2011)
[image omitted] A simple one-pot synthesis has been developed for the synthesis of 2,4,5-trisubstituted imidazoles using an efficient and recyclable MoO3/SiO2 solid acid catalyst by condensation of benzil or benzoin, benzaldehyde, and ammonium acetate in acetonitrile as a solvent. Using this solid catalyst, the reactions could be carried out under mild reaction conditions with very good yield of imidazoles, up to 95%. This catalyst could be recycled very easily, which makes this methodology environmentally benign.
Keywords: benzil; benzoin; cyclocondensation; imidazoles; MoO3; One-pot; SiO2; solid acid